(untitled) (Journal of Fatima Jinnah Medical University, 2026)
palate (CLP) represents one of the most frequent craniofacial malformations. Several international studies have reported an increased frequency of CHD and other associated anomalies among children with CLP, suggesting shared genetic and environmental mechanisms. The objective of this study was to determine the frequency and pattern of congenital heart disease and associated malformations in children with cleft lip and/or palate compared with children without orofacial clefts. Methods: This retrospective case-control study was conducted at a tertiary care cardiac center from September 2021 to September 2024. A total of 646 infants aged less than one year were included, comprising 323 children with CLP (study group) and 323 age- and sex-matched children without orofacial clefts (control group). All participants underwent echocardiographic evaluation. Congenital heart diseases were classified as cyanotic or non-cyanotic, while patent foramen ovale was recorded separately. Demographic variables, risk factors, and associated non-cardiac anomalies were analyzed using Chi-square and Fisher’s exact tests. Results: Congenital heart disease was significantly more frequent in children with CLP compared to controls (27% vs. 5%, p-value<0.001). Non-cyanotic CHDs, particularly septal defects, were the most common. Associated non-cardiac anomalies were observed in 36% of the study group versus 7% of controls (p-value <0.001). Parental consanguinity and maternal smoking were significantly associated with CLP and CHD. Conclusion: Children with cleft lip and/or palate have a significantly increased risk of congenital heart disease and associated malformations. Early echocardiographic screening and comprehensive evaluation are recommended to improve clinical outcomes in this high-risk population